2016
DOI: 10.16965/ijar.2016.197
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Papillary Muscles of the Left Ventricle in the Adult Human Cadavers

Abstract: Normal valve function depends upon the anatomic and mechanical integrity of the atrioventricular ring, the valve leaflets, the chordae tendineae and papillary muscles. Papillary muscle rupture and dysfunction can lead to complications of prolapsed mitral valve and mitral regurgitation. Materials and Methods: The material for present study consisted of 50 formalin fixed adult apparently normal cadaveric hearts belonging to either sex obtained from the Department of Anatomy, Govt. Medical College, Amritsar. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 16 publications
(19 reference statements)
2
6
0
Order By: Relevance
“…In our study, the right and left ventricles of all 50 hearts were found to contain three and two papillary muscles, respectively. Most anatomy textbooks indicate the existence of two papillary muscles in the left ventricle, which is well in accordance with the findings of our study as well as the one conducted by Shree et al [ 12 ]. In rare situations, Oosthoek et al and Madu et al reported an extra papillary muscle lying near to the apex [ 18 - 19 ].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…In our study, the right and left ventricles of all 50 hearts were found to contain three and two papillary muscles, respectively. Most anatomy textbooks indicate the existence of two papillary muscles in the left ventricle, which is well in accordance with the findings of our study as well as the one conducted by Shree et al [ 12 ]. In rare situations, Oosthoek et al and Madu et al reported an extra papillary muscle lying near to the apex [ 18 - 19 ].…”
Section: Discussionsupporting
confidence: 94%
“…The shape of the papillary muscles has an important role in smooth blood flow. In most textbooks, papillary muscles are characterized as conical in form, which is best adapted to facilitate cardiovascular physiology by obstructing the blood flow as little as possible [ 12 ]. In our study, the most common shape we came across among papillary muscles of right ventricles was conical: 42% in anterior, 36% in posterior, and 100% in septal papillary muscles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Te papillary muscles are one of the components of the mitral valve and typically consist of two papillary muscle groups, the anterior papillary muscle group and the posterior papillary muscle group, with various morphological diversities. Several previous studies have reported the morphological evaluation of papillary muscles in donated hearts [1][2][3][4][5][6][7][8][9]. However, these studies were conducted on normal hearts, and hearts with diseases, such as mitral regurgitation (MR), have rarely been investigated.…”
Section: Introductionmentioning
confidence: 99%